Seasonal effects on growth and product quality in Atlantic salmon fed diets containing terrestrial oils as assessed by a long‐term, on‐farm growth trial. (4th December 2020) - Mock, Thomas S.; Francis, David S.; Jago, Matthew K.; Miles, Paige C.; Glencross, Brett D.; Smullen, Richard P.; Keast, Russell S. J.; Turchini, Giovanni M.
Abstract: Seasonal changes in water temperature affect the utilization of dietary fatty acids in Atlantic salmon ( Salmo salar L .). Furthermore, fatty acid profiles of terrestrial oils dictate their suitability in terms of provision of metabolic energy and final product quality. An on‐farm, growth trial of Atlantic salmon was conducted in Tasmania, Australia over the final year of grow‐out (323 days), consisting of a 'summer phase' and a 'winter phase'. Poultry by‐product oil, canola oil and tallow were fed at high dietary lipid inclusion level (80%) to assess growth, fillet fatty acid composition and sensorial attributes. In the summer phase, the tallow diet appeared to provide added substrate for metabolic energy, potentially enhancing the deposition of n‐3 LC PUFA into the fillet, despite lower final weight and a reduced apparent lipid digestibility. Subsequent winter phase results suggested all diets adequately provided metabolic energy and fillet n‐3 LC PUFA concentrations were comparable. Additionally, this study highlights the importance of a well‐considered experimental design and subsequent statistical interpretation, for commercial scale, on‐farm feeding trials. Ultimately, this study demonstrates the importance of seasonally tailored diets for Atlantic salmon, using high terrestrial oil inclusion, under challenging Australian farming conditions.